TOLERÂNCIA AO CALOR DE BOVINO PANTANEIRO - BEZERRA, Thais dos Santos; SANTOS, Marrony Gonçalves Pires; OLIVEIRA. Pedro Henrique Pereira de; FERREIRA, Andre Lima; VILELA, Reissa Alves; SANTOS, Tania Mara Baptista (ANAIS DO ENIC, 2024)
-